Current understanding of the origin, molecular biology and continuing evolution of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) - Mohamad Saifudin Hakim; Luthvia Annisa; Endah Supriyati; Edwin W. Daniwijaya; Rakhmat A. Wibowo; Eggi Arguni; Titik Nuryastuti (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2020)
Recent outbreaks of human coronaviruses, officially named severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), have put health authorities worldwide on a high alert. Firstly emerged in the city of Wuhan, China, SARS-CoV-2 infection is rapidly escalating into a global pandemic. It is first thought as the result of a zoonotic transmission event, similar to the previous epidemic of coronaviruses. However, a continuously increasing number of confirmed cases indicates that the virus gains capacity of efficient human-to-human transmission. Soon after the pandemic is arising, many efforts are focused on identifying the origin of SARS-CoV-2 infection in the human population. Current evidence suggests that the virus is probably derived from bat or pangolin coronaviruses as the natural host. Whether intermediate host(s) exist in the transmission cascade from bat or pangolin to humans is, to a great extent, elusive. This information is essential as the basis for infection prevention and control measures. In this review, we discuss our recent understanding of SARS-CoV-2 biology, highlighting its origin and molecular evolution.